The Role of Social Learning in the Evolution on a Rugged Fitness Landscape - Higashi, Masahiko; Suzuki, Reiji; Arita, Takaya (Frontiers in Physics, 2018)
The role and importance of social learning have been investigated by many researchers because it is observed in many animals and is expected to play a significant role in cultural phenomena. We explore the coevolution between individual learning and social learning on a rugged fitness landscape as a realistic condition in which they can interact with each other. We demonstrate that social learning allows individuals not to have adaptive traits innately, and thus, has two important roles to enhance individual fitness. First, social learning spreads and keeps the adaptive phenotypes acquired by individual learning. Second, social learning enables individuals to explore a wide range of fitness landscape by the increased population diversity. Based on the difference of the roles of individual and social learning, they can work complementarily in the course of adaptive evolution on the rugged fitness landscape.